2017
DOI: 10.1038/s41598-017-11521-5
|View full text |Cite
|
Sign up to set email alerts
|

Interference of stress with the somatotropic axis in pigs – lights on new biomarkers

Abstract: The acceptance of animal products is increasingly associated with standardized animal welfare, which relates to appropriate animal husbandry from birth to slaughter. In particular, shipment to the slaughterhouse is considered as a critical process exposing the animals to a number of, in part severe, stressors. New biomarkers may be useful for the assessment of animal welfare. The IGF-system has been assessed in a commercial pig transport in conjunction with established markers of stress response. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
5
8
1
Order By: Relevance
“…Food was removed from pigs transported for 6 and 12 or 18 h for 20 and 24 h, respectively. As previously described, fasting did not affect the circulating levels of IGF-1 and IGFBPs within the time frame of this experiment ( 9 ). The pigs had no access to water on the truck, but water was available in lairage.…”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…Food was removed from pigs transported for 6 and 12 or 18 h for 20 and 24 h, respectively. As previously described, fasting did not affect the circulating levels of IGF-1 and IGFBPs within the time frame of this experiment ( 9 ). The pigs had no access to water on the truck, but water was available in lairage.…”
Section: Methodssupporting
confidence: 78%
“…The collection of exsanguination blood directly after the slaughtering of pigs is a suitable, non-invasive technique for the evaluation of the physiological response to different transport durations and preslaughter conditions. As described in preliminary studies ( 9 ), cortisol concentrations, measured in exsanguination blood, were not affected after prolonged duration of shipment. Though, insulin-like growth factor-binding protein (IGFBP)-2 concentrations decreased over time due to the length of shipment indicating biomarker potential for components of insulin-like growth factor (IGF) system.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…For instance, in response to 5 minutes of restraint, circulating IGF-1 levels decreased by 21% within 60 minutes in Yorkshire pigs Sus crofa domesticus and remained suppressed for up to 150 minutes (Farmer et al, 1991). A more recent study in pigs also found that restraint stress caused a drop in circulating IGF-1 levels and affected other components of the IIS pathway, suggesting that the IGFsystem represents a physiologically relevant biomarker of stress response (Wirthgen et al, 2017).…”
Section: Introductionmentioning
confidence: 97%